2013
DOI: 10.1007/s11434-013-5666-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in flow-based sample pretreatment for the determination of metal species by atomic spectrometry

Abstract: During the last few years, various flow-based separation/preconcentration methodologies have gained pertinent novel advances and exhibited powerful capability in the field of sample pretreatment and their hyphenation with detection by atomic spectrometry. The present mini-review presents and discusses the progress of flow-based sample processing approaches commonly used for the assay of trace elemental species with detection by atomic spectrometry, including preliminary sample pretreatment, solid phase extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…This study concluded that it is a very challenging task to detect heavy metals in water in real time due to the interference of large chemical and biological species in water. Yu and Wang [ 141 ] reviewed the determination of metal ions including mercury by atomic spectrometry by applying flow-based sample pretreatment methods. They concluded that the ICP-AES, AAS, AFS, and ICP-MS are the major detection techniques for trace metal analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study concluded that it is a very challenging task to detect heavy metals in water in real time due to the interference of large chemical and biological species in water. Yu and Wang [ 141 ] reviewed the determination of metal ions including mercury by atomic spectrometry by applying flow-based sample pretreatment methods. They concluded that the ICP-AES, AAS, AFS, and ICP-MS are the major detection techniques for trace metal analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These include low consumption of solvents and reagents and thus low cost of total analysis as well as a significant improvement of the repeatability of the extraction procedure. The combination of flow injection analysis (FIA), sequential injection analysis (SIA), and related techniques with atomic spectrometry (AS) [6,39] provide unique capabilities and enhanced performance of the developed methods. Despite the numerous advantages of the FPSE technique, there is a need for automation in order to reduce sample preparation time extremely and considerably improve the analytical characteristics of each developed method.…”
Section: Automated Fabric Phase Sorptive Extractionmentioning
confidence: 99%
“…Even consolidated methods like Spectrometric (CV‐AAS, AEF, and CV‐AFS), chromatographic and potentiometric technologies, with low detection limits (LoD) of about 1 μgL −1 or 1 part per billion (ppb), and a wide linear range for arsenic detection, present some drawbacks in terms of test time, expensive reagents, the need for sample pre‐concentration, lab constraints related to bulky instrumentation, and the need for highly trained personnel (Bose et al, 2011; United States Environmental Protection Agency Office of Water, 1999; Yu & Wang, 2013). Utrasensitive method (LoD of 0.14 ppb) by colorimetric and surface‐enhanced Raman (SERS) using glutathione functionalized Au‐nanoparticles (Li et al, 2020) and rapid colorimetric assay on paper‐based microfluidic device have been described (Martinez et al, 2010; Morita & Kaneko, 2006).…”
Section: Introductionmentioning
confidence: 99%